2020
DOI: 10.5812/numonthly.102860
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Twinkling Artifact Sign Seen in Color Doppler Ultrasonography in Detecting Microlithiasis of Kidney

Abstract: Background: Ultrasonography (US) is a safe and cost-efficient modality which is used to assess patients with urinary tract lithiasis. Objectives: In this study, we aimed to evaluate the accuracy of the twinkling artifact of color Doppler sonography in detecting renal stones smaller than 4 mm in diameter. Methods: Of all patients referring to a tertiary medical center with a probable diagnosis of urolithiasis during April 2019 to September 2019, 99 patients with a renal stone smaller than 4 mm in non-contrast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They found that the TA sign had low specificity (40%) with a high falsepositive rate due to sonographer technique and ultrasound setting, along with high echogenicity of the adjacent renal sinus and renal arterial calcifications, as did Dillman et al [31]. Moreover, the size of the stone could have an influence on the comparison between TA sign and noncontrast CT. Letafati et al [6] evaluated the accuracy of TA in detecting renal stones smaller than 4 mm and found rather low sensitivity (76.8%) but high specificity (100%); therefore, they concluded that TA was a reliable sign for detecting renal calculi smaller than 4 mm. However, this sign could be combined with echogenic focus and posterior acoustic shadow to increase the sensitivity.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the TA sign had low specificity (40%) with a high falsepositive rate due to sonographer technique and ultrasound setting, along with high echogenicity of the adjacent renal sinus and renal arterial calcifications, as did Dillman et al [31]. Moreover, the size of the stone could have an influence on the comparison between TA sign and noncontrast CT. Letafati et al [6] evaluated the accuracy of TA in detecting renal stones smaller than 4 mm and found rather low sensitivity (76.8%) but high specificity (100%); therefore, they concluded that TA was a reliable sign for detecting renal calculi smaller than 4 mm. However, this sign could be combined with echogenic focus and posterior acoustic shadow to increase the sensitivity.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Many diagnostic methods have been thought to aid in identifying urolithiasis, including plain radiography, intravenous pyelourethrography, ultrasonography (US), and computed tomography (CT) [5]. Unenhanced CT scanning is broadly considered the current gold standard for the diagnosis of urolithiasis [6]. Noncontrast CT is the most sensitive (up to 98%) and specific (96-100%) method for the detection of urinary stones [7].…”
Section: Introductionmentioning
confidence: 99%